Clinico-Pathological Characteristics and Mutational Analysis of Gastrointestinal Stromal Tumors from India: A Single Institution Experience - Minhas, Sachin; Bhalla, Sunita; Jauhri, Mayank; Ganvir, Madhusudan; Aggarwal, Shyam (Asian Pacific journal of cancer prevention : APJCP, 2019)
Gastrointestinal stromal tumor (GIST) is the most common type of mesenchymal neoplasm of gastrointestinal tract. The incidence of GIST in India is not known and its treatment strategy in our country is largely derived from studies in other global populations. Some of the most important features of this type of cancer include its size, site of origin, mitotic index, histology and Immunohistochemistry. In this report we have studied these parameters in the Indian GIST patients presenting at our center. Additionally, we have also studied the mutational spectrum of these GISTs by next generation sequencing. Thirty one Indian patients of GIST were enrolled in this study and information regarding age, gender, tumor location and size was collected from their records. Immunohistochemistry studies were performed by the pathologist. Mutational analysis of these samples was performed by next generation sequencing. The most common site of GIST occurrence in our study was stomach. The tumor size for all 31 patients ranged between 0.6 cms to 20 cms. A spindle-cell pattern was present in 24 out of 31 of the cases. 29 out of 31 subjects were positive for CD117 expression. C-KIT was the most highly mutated gene indentified in our patients. Apart from these findings we observed many similarities as well as dissimilarities between the results of our study and literature published previously. The dissimilarities in the results of our study and published literature could be attributed to the genetic or ethnic differences that exist between the Indian population and other global populations. The results of our study warrant a need to conduct studies of GIST in a much larger population of India. Such large scale studies may also help in better treatment and/or prevention of GIST in developing countries like India.